2017
DOI: 10.1080/03019233.2017.1303933
|View full text |Cite
|
Sign up to set email alerts
|

Modelling inclusion evolution in Al–Ti-killed steels during ladle mixing process

Abstract: A reaction model was developed to better understand the evolution of inclusions in Al-Ti-killed steels during the ladle mixing process. The fluctuation of steel chemistry gave rise to the transient evolution of inclusions during the mixing process. The formed Al 2 O 3 in the steel can be hardly influenced by the addition of FeTi, while adding Al can effectively modify the TiO xcontaining oxides to solid Al 2 O 3 . The formation of Al 2 O 3 -TiO x inclusions can be suppressed by increasing Al and lowering Ti in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…These newly produced Ti-bearing particles may increase the Ti loss because of the adsorption of refining slag in practical production. Hence, along with the steel chemistry (Al, Ti, and O contents) [39], the morphology of existing Al 2 O 3 -based inclusions is a contributing factor affecting the Ti yield. This means the large Al 2 O 3 -based particles including larger aggregates, clusters, and some flower-shaped inclusions, should be eliminated by stirring to the extent possible before Ti addition.…”
Section: Three-dimensional Characteristics Of Inclusions After Ti Addmentioning
confidence: 99%
See 1 more Smart Citation
“…These newly produced Ti-bearing particles may increase the Ti loss because of the adsorption of refining slag in practical production. Hence, along with the steel chemistry (Al, Ti, and O contents) [39], the morphology of existing Al 2 O 3 -based inclusions is a contributing factor affecting the Ti yield. This means the large Al 2 O 3 -based particles including larger aggregates, clusters, and some flower-shaped inclusions, should be eliminated by stirring to the extent possible before Ti addition.…”
Section: Three-dimensional Characteristics Of Inclusions After Ti Addmentioning
confidence: 99%
“…Second, although various factors including the sequence of alloy addition [18,20,32,33], titanium source [34], titanium/aluminum ratio [35], and element contents [19,[36][37][38][39] have been examined their impacts on the inclusion behaviors during Al and Ti additions, several fundamental questions remain about the evolution mechanism of the inclusion behaviors. In a laboratory study of deoxidation by Al and Ti at 1873 K, Nagata et al [40] found that alumina particles were formed with an acicular shape at first and gradually changed to clusters of granular Al 2 O 3 spheres, but the inclusion characteristics were, nevertheless, not significantly affected by the subsequent Ti feeding.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the ladle furnace is divided into several tanks that are circulated using the stirring energy generated by an Ar flow. This model can predict compositional changes in molten steel, slag, and inclusions, such [16][17][18][19] developed a kinetic model based on FactSage macro processing to predict the formation of inclusions using Alkilled steel and Al-Ti-killed steel. The reactions between steel and inclusions were assumed to be equilibrated, and the reactions between bulk area and interface area in steel and slag were simulated by mass transfer.…”
Section: Evolution Of Mg-al-based Inclusions With Changes In Mg Contementioning
confidence: 99%
“…In previous models, the generation of spinel was simulated when the mole fraction of MgO and Al 2 O 3 in the spinel was halved and the activity in the spinel was fixed. [12][13][14][15][16][17][18][19][20][21][22] However, in the proposed enhanced model, the activities of Al 2 O 3 , MgO, and spinel change with increasing MgO content in Mg-Al-based inclusions.…”
Section: Generation Of Mgal 2 O 4 and Mgo Inclusions Through Reactionmentioning
confidence: 99%
“…The predicted inclusion development and compositions of steel and slag agreed well with the industrial practice from 210 and 30 ton ladle treatment. Additionally, similar models were also developed by the researchers with the specified targets due to the high efficiency, [9][10][11][12][13][14][15][16][17] as shown in Table 1. 1) Most researchers used commercial software (FactSage, Metsim, ChemApp, and SimuSage) for thermodynamic calculations, whereas the empirical models offer a faster calculation speed.…”
Section: Introductionmentioning
confidence: 99%